DETERMINATION OF THE DYNAMIC MODULUS OF LINEAR DEFORMATIONS OF REINFORCED HIGHLY FILLED POLYMER CONCRETE COMPOSITES DURING CURING (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The objects of this study are reinforced polymer concrete composites with epoxy matrix and mineral dispersion fillers. Dynamic modulus of linear deformations has been measured according the standardized dynamic testing method ASTM E1876 - 02. The quantitative values of the modulus are obtained by the action of longitudinal and bending. After statistical processing of the obtained results has been established the influence of fiber in the composition on the dynamic characteristic.